(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
this article shows the design of the experimental sample, the load capacity of raw materials is 50 kg, air heaters with a total area of 7 m2 for solar dryers were carried out supporting experimental work for agricultural products. During the experiment, the results showed that time (26 hours) apples were dried to 15% moisture, pears showed a result of 25%, and control samples-42-45%. Temperatures were determined, the results were achieved when heating the air in the dryer from the sun at a power of 2 kWh, that is, 1300 m3/h. In the course of the experiment, these results became known that the disadvantages and descriptions of the designed solar dryer were described in detail.